Texts and contexts of the Book of Sirach = Texte und Kontexte des Sirachbuches - Zapff, Burkard M. 1960- (Septuagint and cognate studies, 2017)
"Thirteen essays, some in German and others in English, tackle the complicated history of textual transmission of the Book of Ben Sira. This book presents the proceedings of an international conference held in 2014 in Eichstaett/Germany on the text of Ben Sira within its historical contexts"...